1980
DOI: 10.1002/1097-0142(19801015)46:8<1868::aid-cncr2820460827>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pulmonary scar carcinomas in a patient with Hodgkin's Disease: Report of a case and review of the literature

Abstract: A case of multiple pulmonary scar carcinomas arising in a 53-year-old woman with Hodgkin's disease is reported. Review of the literature reveals that scar carcinoma is generally thought to arise in areas of bronchiolar epithelial proliferation occurring in association with pre-existing lung scars. However, we and others have emphasized that, given the usual gross and histologic picture of scar carcinoma, it is impossible to state with certainty whether the carcinoma arose in response to the scar tissue, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has been suggested that fibrosis may occur as a desmoplastic reaction to an already existing carcinoma similar to that occurring in breast carci-noma. [27][28][29][30] On the other hand, it has recently been shown in experimental studies that chronic tuberculosis infection induces cell dysplasia and squamous cell carcinoma in a lungspecific way. 31 In a retrospective autopsy study of 82 lung cancer cases associated with a scar, Auerbach et al 7 documented 23% being associated with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fibrosis may occur as a desmoplastic reaction to an already existing carcinoma similar to that occurring in breast carci-noma. [27][28][29][30] On the other hand, it has recently been shown in experimental studies that chronic tuberculosis infection induces cell dysplasia and squamous cell carcinoma in a lungspecific way. 31 In a retrospective autopsy study of 82 lung cancer cases associated with a scar, Auerbach et al 7 documented 23% being associated with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 Others, however, have reported that the carcinoma-related scar is an example of desmoplastic reaction such as is seen in breast, stomach, pancreas, and colon cancers. [5][6][7] It is generally agreed the pulmonary adenocarcinoma has a lower survival rate than squamous cell carcinoma, because the tumor often invades both lymphatic channels and blood vessels at a very early stage in its development7 8 and also produces symptoms later in the course of the disease. Therefore, it becomes worthwhile to investigate the origin and significance of the fibrosing process associated with pulmonary scar carcinoma.…”
mentioning
confidence: 99%